2003
DOI: 10.1073/pnas.0237359100
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Fas to diabetes development

Abstract: Fas (Tnfrsf6, Apo-1, CD95) is a death receptor involved in apoptosis induced in many cell types. Fas have been shown to be expressed by insulin-producing beta cells in mice and humans. However, the importance of Fas in the development of autoimmune diabetes remains controversial. To further evaluate the importance of Fas in pathogenesis of diabetes, we generated NOD mice (nonobese diabetic mice developing spontaneous autoimmune diabetes) with beta cell-specific expression of a dominant-negative point mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 37 publications
2
66
0
1
Order By: Relevance
“…Savinov et al (12), on the other hand, have shown that Fas is involved in ␤-cell death in a model where diabetes is accelerated by FasL expression on ␤-cells. However, it is not clear how/whether this system translates to the normal context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Savinov et al (12), on the other hand, have shown that Fas is involved in ␤-cell death in a model where diabetes is accelerated by FasL expression on ␤-cells. However, it is not clear how/whether this system translates to the normal context.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in vivo treatment of mice with an anti-FasL antibody (11) or in whom a dominant-negative Fas mutation has been introduced (12) seems to suggest that Fas may contribute to the early stages of the disease. On the other hand, inactivation of the Fas gene, specifically in ␤-cells, has not prevented disease in a model where T-cells expressing a transgeneencoded T-cell receptor (TCR) specific for influenza hemagglutinin (HA) mediate diabetes in mice that express the HA peptide in ␤-cells (13).…”
mentioning
confidence: 99%
“…Autoimmune destruction of b-cells is for the most part due to induction of apoptosis (28,29) by cytokines such as interleukin (IL)-1b, tumor necrosis factor (TNF)-a, and interferon (INF)-c , which are secreted in the vicinity of the islets by activated T-lymphocytes (9,10). Overexpression of antiapoptotic genes by in vivo gene delivery into prediabetic animals could increase b-cell resistance to these cytokines.…”
Section: Strategies For Gene Therapy In Iddmmentioning
confidence: 99%
“…Transgenic NOD mice, expressing dominant negative Fasassociated death domain (FADD), had limited protection ( Table 1). FADD is a component of the Fas signaling pathway that only occurs in beta-cells and transgenic mice containing a beta-cell-specific disruption of Fas [101,102]. Similarly, islets deficient in Fas expression were not protected in CD4 T cell-induced diabetes, suggesting beta-cell destruction occurs in the absence of a functional Fas pathway [103,104].…”
Section: The Fas/fasl Pathway Is a Minor Effector Of Beta-cell Destrumentioning
confidence: 99%